Symmetrical Catalytic Colloids Display Janus‐Like Active Brownian Particle Motion - Richard J. Archer; Stephen J. Ebbens (Advanced Science, 2023)
Abstract Catalytic Janus colloids, with one hemi‐sphere covered by a hydrogen peroxide reduction catalyst such as platinum, represent one of the most experimentally explored examples of self‐motile active colloid systems. This paper comparatively investigates the motile behavior of symmetrical catalytic colloids produced by a solution‐based metal salt reduction process. Despite the significant differences in the distribution of catalytic activity, this study finds that the motion produced by symmetrical colloids is equivalent to that previously reported for Janus colloids. It also shows that introducing a Janus structure to the symmetrical colloids via masking does not significantly modify their motion. These findings could indicate that very subtle variations in surface reactivity can be sufficient to produce Janus‐like active Brownian particle‐type motion, or that a symmetry‐breaking phenomena is present. The study will consequently motivate fresh theoretical attention and also demonstrate a straightforward route to access large quantities of motile active colloids, which are expected to show subtly different phenomenology compared to those with Janus structures.